Adaptive system for visualization of the electromagnetic scattering field of aircraft - Z. M. Kurbanismailov; A. T. Tarlanov; E. D. Matyash; E. S. Karbova (Российский технологический журнал, 2021)
The space industry has always set ambitious tasks to create unique equipment, including control equipment. Ensuring electromagnetic compatibility (EMC)  of  such systems is carried out at all stages of the life cycle of an aircraft (AC), starting from its development, including testing and stages of  operation. Digital technology is characterized by high noise immunity.  However, any modern technical system in the aggregate contains sensors, communication lines and receiving  antennas sensitive to the effects of external interfering signals that propagate both through wires and over the air. Hence, the relevance of ensuring the EMC of integrated technical systems that perform the functions  of  measurement, data processing and the formation of control actions, both digital and analog, is obvious. The electromagnetic compatibility of a sophisticated aircraft or spaceship technical system with other systems is a prerequisite for their sustainable operation. Aerospace technology, where both highly sensitive measurements and energetic control effects are closely combined in the dense layout of an aircraft, requires a solution to the EMC problem. This paper shows the need for effective technology to control the electromagnetic radiation created in the surrounding space, both by subsystems of aircraft and by the whole object. A method for visualizing 3D electromagnetic field both in space and in time is considered.